Hubungan Spiritual Well-Being Dengan Resiliensi Mahasiswa Kedokteran Pada Masa Pandemi Covid-19 - Salamy, Ach. Yarziq Mubarak Salis; Salamy, Ahmed Zaiyan Nahel; Salamy, Nanda Fadhilah Witris; Salamy, Muhammad Fath Alhaqqi Sanis; Lisnawati, Diana Arum (Jurnal sosial dan sains, 2025)
The most severe pressure for most final semester students is to complete a thesis or final project to get a bachelor's degree—this increased pressure experienced by final-semester students. The conditions of the COVID-19 pandemic have a significant mental impact. One way to help overcome pressure is resilience, which is a person's ability to survive, adapt, and develop in overcoming obstacles or difficulties. A good level of spiritual well-being (SWB) will make it easier to solve the problems faced. Previous research shows there is a causal relationship between SWB and resilience in helping individuals deal with stress and providing protection against depression and anxiety. This study aims to determine the relationship between SWB and resilience in final-semester students working on their thesis, especially during the Covid-19 pandemic. This study is an analytic observational study that aims to examine the relationship between spiritual well-being and resilience. Data was collected from 119 respondents through the online Malay Version of the Spiritual Well-Being Scale and Brief Resilience Scale (BRS) questionnaires. Analysis was done descriptively, then the relationship between variables was analyzed using Spearman's correlation. This study reveals a significant correlation between Religious Well-being and resilience level, with a correlation coefficient of 0.269 and a p-value of 0.003. Similarly, a significant relationship was found between Existential Well-being and the Brief Resilience Scale, with a correlation value of 0.374 and a significance level of 0.000. A significant relationship exists between SWB and student resilience during the COVID-19 pandemic, with a moderate correlation level (0.368) and a significant correlation coefficient (0.00003).